2007
DOI: 10.11646/zootaxa.1615.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Sycanus aurantiacus (Hemiptera: Heteroptera: Reduviidae), a new harpactorine species from Bali, Indonesia, with brief notes on its biology

Abstract: A new species, Sycanus aurantiacus, of the assassin bug subfamily Harpactorinae is described on the basis of specimens collected from Bali, Indonesia. This species is distinguished from the other species of Sycanus by its antennal segment I having two orange annulations; the posterior pronotal lobe being weakly tumid in the middle near the posterior margin; the scutellar spine being erect, short, and rounded at the apex; each femur having two incomplete orange annulations; the hemelytral corium being blackish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…S. aurantiacus was found (in 2019) in a farmer's plastic house in the Bedugul region of Bali, in an area of especially abundant moss in Pancasari Village. The observation differed somewhat that described previously by Ishikawa et al (2007) and Yuliadhi et al (2015) who reported that the species was an important predator of some key lepidopteran cabbage pests. However, now the species was being found in abundance in farmer's plastic house containing various crops.…”
Section: Sequence Similarity and Phylogenycontrasting
confidence: 99%
See 1 more Smart Citation
“…S. aurantiacus was found (in 2019) in a farmer's plastic house in the Bedugul region of Bali, in an area of especially abundant moss in Pancasari Village. The observation differed somewhat that described previously by Ishikawa et al (2007) and Yuliadhi et al (2015) who reported that the species was an important predator of some key lepidopteran cabbage pests. However, now the species was being found in abundance in farmer's plastic house containing various crops.…”
Section: Sequence Similarity and Phylogenycontrasting
confidence: 99%
“…A new species Sycanus aurantiacus Ishikawa & Okajima was discovered in 2004 by researchers conducting a project on "Development of New Bio-Agents for Alternative Farming Systems" conducted by the Tokyo University of Agriculture in collaboration with Udayana University. The new harpactorine species from Bali was first formally described in a publication in 2007, based primarily on morphological characteristics (Ishikawa et al 2007). S. aurantiacus was observed in cabbage plantations across the Bedugul region, including Pancasari (which lies more than 1,000 m above sea level).…”
Section: Introductionmentioning
confidence: 99%
“…Phallus (P) Intromittent organ inside the pygophore Phallus (Ph) (P) Lent and Jurberg 1984;Lent and Jurberg 1987;Lent et al 1993a, b;Mejia et al 1999;Carcavallo et al 2001;Valente et al 2001;Cai and Tomokuni 2003;Ishikawa et al 2007;Sandoval et al 2007;Weirauch 2008;Jurberg et al 2009;Frías-Lasserre 2010;Forero et al 2010;Forero and Weirauch 2012;Rosa et al 2012;Gonçalves et al 2013;Gil-Santana and Galvão 2013;Jurberg et al 2013;Castro-Huertas and Forero 2014;Zhao et al 2015 Lent and Jurberg 1984;Lent and Jurberg 1987;Lent et al 1993;Mejia et al 1999;Carcavallo et al 2001;Valente et al 2001;Sandoval et al 2007;Gonçalves et al 2013;…”
Section: Previously Used Terms Referencesmentioning
confidence: 99%
“…The genus Sycanus was established by Amyot & Serville in 1843 for the oriental species, Reduvius collaris Fabricius, 1781 as the type species, with seventy-six Oriental and one Madagascar known species [22][23][24][25]. The beautiful assassin bugs are easily separated from other allied genera by the following characters: the head is much longer than the pronotum, the scutellum is apically armed with a spine or tubercle, and the connexivum of abdomen is extremely laterally dilated.…”
Section: Introductionmentioning
confidence: 99%